Digital Literacy Integration: Training On Using The Turats Book Search Website For Students Based In Islamic Boarding Schools - Syafa'ah, Lailatus; Albab, Ahmad Ulil; Nabiel, Mohammad (At Taawun Bangun Bangsa, 2025)
This study aims to analyze the digital literacy level of students majoring in Qur'anic Studies and Interpretation at IAI Badrus Sholeh, who are located in a boarding school environment, and to examine the effectiveness of training in the use of websites for searching for classical Islamic texts as an effort to improve academic competence. The pre-test results show that students' digital literacy is still low to moderate, especially in terms of access to and utilization of digital scientific resources, while the use of digital media is mostly limited to general needs such as social media. The training was conducted in stages through workshops, book search practices, group discussions, and mentoring, which equipped students with conceptual understanding as well as technical skills in optimizing the classical book website. The post-test evaluation showed a significant increase in both technical skills and changes in students' attitudes towards the importance of digital literacy in scientific studies. These findings confirm that the integration of digital literacy through structured training can strengthen the academic tradition of Islamic boarding schools by combining classical scientific heritage (turats) and the use of modern technology. Conceptually, this research contributes to the development of an Islamic education model that is adaptive to the demands of the digital era without abandoning the roots of the Islamic boarding school tradition.